1995
DOI: 10.1111/j.1474-919x.1995.tb08039.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth, fledging success and post‐fledging survival of juvenile Oystercatchers Haematopus ostralegus

Abstract: We studied the consequences of differences in growth rate on the subsequent survival of Oystercatcher Haernatopus ostralegus chicks. Fledging success increased sharply with growth rate, from zero in chicks growing at less than 6 g per day to about 85% in chicks growing at more than 10 g per day. The age at which chicks fledged varied from 27 to 52 days. Chicks which fledged at an early age displayed a much faster growth rate than later fledging chicks. Although slow growth resulted in a considerable prolongati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 35 publications
2
36
0
Order By: Relevance
“…Chick mortality is most common at an early age in other oystercatcher species as well. In a study of Eurasian Oystercatchers, Kersten and Brenninkmeijer (1995) found that only 44% of chicks survived to 12 days old. Hazlitt and Butler (2001) also found mortality to be highest within the first week after hatching in Black Oystercatchers (H. bachmani).…”
Section: Discussionmentioning
confidence: 99%
“…Chick mortality is most common at an early age in other oystercatcher species as well. In a study of Eurasian Oystercatchers, Kersten and Brenninkmeijer (1995) found that only 44% of chicks survived to 12 days old. Hazlitt and Butler (2001) also found mortality to be highest within the first week after hatching in Black Oystercatchers (H. bachmani).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, for population models more data on the proportion of adults that start breeding are badly needed, together with the occurrence of replacement clutches and data on dispersal, immigration and emigration. Neve and Van Noordwijk (1997), (9) Kersten and Brenninkmeijer (1995), (10) Le V.Dit Durell et al (2000), (11) Hulscher (1989), (12) Safriel et al (1984), (13) Harris (1970), (14) Schnakenwinkel (1970), (15) Boyd (1962), (16) Grosskopf (1964), (17) Jungfer (1954) in Boyd (1962) See Table 7. Abbreviations: see Appendix 2…”
Section: Conclusion and Recommendationsmentioning
confidence: 96%
“…After leaving the nest, chicks are tended by parents for varying periods, during which time they become increasingly independent. As they age, chicks become more proficient at thermoregulating (Visser and Ricklefs 1993, Schekkermann and Visser 2001, Schekkermann et al 2003, foraging (Kersten and Brenninkmeijer 1995), and evading predators (Powell 1992). A consequence of this increasing independence is a tendency for chick survival to increase with age.…”
Section: Introductionmentioning
confidence: 99%